2018
DOI: 10.1509/jm.16.0169
|View full text |Cite
|
Sign up to set email alerts
|

When Celebrities Count: Power Distance Beliefs and Celebrity Endorsements

Abstract: The use of celebrity endorsements varies across countries; does their effectiveness similarly vary across cultures? The authors propose that power distance beliefs (PDB), a cultural orientation related to the extent to which people expect and accept differences in power, moderate the effects of celebrity endorsements. A positive effect of celebrity endorsers on evaluations of advertising should be more potent with greater PDB; source expertise and trustworthiness likely underlie this effect. To test the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 64 publications
(109 reference statements)
4
90
0
4
Order By: Relevance
“…In Experiment 1, we examine the hypotheses in a celebrity vs. ordinary consumer endorser context. As previous literature points out, celebrities are authority figures [7] who possess higher social status than do ordinary consumers [6], therefore, we try to explore whether this discrepancy in social status between celebrities and ordinary consumers would affect endorsement effectiveness when paired with different forms of normative appeals as predicted in the hypotheses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Experiment 1, we examine the hypotheses in a celebrity vs. ordinary consumer endorser context. As previous literature points out, celebrities are authority figures [7] who possess higher social status than do ordinary consumers [6], therefore, we try to explore whether this discrepancy in social status between celebrities and ordinary consumers would affect endorsement effectiveness when paired with different forms of normative appeals as predicted in the hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“…In Experiment 2, we asked participants to evaluate the endorsers for social status to serve as manipulation checks (a 7-point semantic differential item). As prior literature suggests, social status could affect endorser trustworthiness and attractiveness [5, 7], which are predictors of endorsement effectiveness [14, 17]; therefore, we also asked participants to evaluate the endorsers for attractiveness and trustworthiness (each with one 7-point semantic differential item) to rule out the alternative explanations. In addition, we measured the environmental knowledge of the participants as control variables with scales used in Experiment 1 (Cronbach’s α = .79).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Choi, Lee, and Kim () and Biswas et al () argued that endorsement research has been mainly conducted in the context of source credibility and attractiveness theory, and thus endorsements are typically found to be effective due to the source's credibility and attractiveness. Similarly, Winterich, Gangwar, and Grewal () interpreted research findings as evidence that trustworthiness and expertise (the two components of credibility) are the most influential determinants of the effect of celebrity endorsers on evaluations, whereas Zwilling and Fruchter () observed that in most cases, it is the attractiveness of the celebrity that strengthens consumer intention to purchase the advertised product.…”
Section: Evolution Of Endorsement Theory and Advertising Praxismentioning
confidence: 99%
“…This attribute constrains its efficiency of obtaining the common and robust conclusions about product endorsement from management or marketing perspective. Evidences show that the effects of celebrity endorsements vary across countries and cultures (Winterich, Gangwar, & Grewal, 2018). On the contrary, economics has the inherent strength of revealing common and robust economics behaviours.…”
Section: Introductionmentioning
confidence: 99%